Factors related to hyperemesis gravidarum in pregnant women at Siti Aisyah hospital Lubuklinggau city 2023 - Fitriani, Dita Dwi; Suprida, Suprida; Novita, Nesi (Journal of Maternal and Child Health Sciences (JMCHS), 2024)
Every woman wants to be a mother, but this is very important for a wife who is married and wants to have a child. In some cases, undesrable things happen during pregnancy, this creates chaos for couples who are facing a pregnancy that threatens the life of the mother, from the time the pregnancy begins and the fetus is carried until it is born. Excessive nausea and vomiting can interfere with daily work activities and the condition can eventually become dangerous vomiting symptoms, which are different from normal Morning Sickness which is usually experienced and occurs during the first trimester of pregnancyTo determine the factors that influence the occurrence of Hyperemesis Gravidarum in Pregnant Women at RSUD Siti Aisyah Lubuklinggau City in 2023. This type of research uses a quantitative descriptive method for analyzing cross-sectional research plans. The research was carried out in the month of April-May 2024. The population in this research consisted of 234 pregnant women. This research identified the risk factors that influence the occurrence of Hyperemesis Gravidarum, namely maternal age, p-value 0.002 (< 0.05), maternal parity value p-value 0.002 (< 0.05), mother's job p-value 0.001 (< 0.05), maternal gestational age p-value 0.002 (< 0.05). This research concludes that there is a significant difference in meaning in age, parity, employment, and age of maternal gestation with Hyperemesis Gravidarum. It is recommended that health services increase promotion of pregnant women directly through ANC (Antenatal Care) consultations.